2022
DOI: 10.3390/youth2030022
|View full text |Cite
|
Sign up to set email alerts
|

Conscientisation and Radical Habitus: Expanding Bourdieu’s Theory of Practice in Youth Activism Studies

Abstract: Bourdieu’s theory of practice is a useful tool to understand people’s everyday behaviours, dispositions and habits. However, this theory struggles to explain how some people diverge from the social norms that structure their habitus. This article proposes an extension of Bourdieu’s theory of practice by incorporating Freire’s conscientisation, that is, a theory of how individuals develop a critically conscious awareness through engagement with the world around them. Here, we use young people’s engagement in ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…has not yet been published for the 2019 election, in 2016 LGBTI representation stood at 3 per cent in the House of Representatives and 5 per cent in the Senate (compared, for example, with the UK, which had 6.9 per cent LGBTI representation in the House of Commons after the 2017 election). 66 Studies of electoral systems across the world have shown that proportional representation systems (as in the Senate) have a positive effect on the election of female candidates, compared with majoritarian systems with single-member electorates (as in the House of Representatives). 68 This can be seen in the Australian…”
Section: Representation In Parliaments and Cabinetsmentioning
confidence: 99%
See 2 more Smart Citations
“…has not yet been published for the 2019 election, in 2016 LGBTI representation stood at 3 per cent in the House of Representatives and 5 per cent in the Senate (compared, for example, with the UK, which had 6.9 per cent LGBTI representation in the House of Commons after the 2017 election). 66 Studies of electoral systems across the world have shown that proportional representation systems (as in the Senate) have a positive effect on the election of female candidates, compared with majoritarian systems with single-member electorates (as in the House of Representatives). 68 This can be seen in the Australian…”
Section: Representation In Parliaments and Cabinetsmentioning
confidence: 99%
“…First practised by Swedish teenager Greta Thunberg in 2018 before spreading globally, the school strike movement saw young people mobilising to call for more ambitious and urgent policy action on climate change. 66 The movement, led and driven by young people (who are largely excluded from conventional political participation, such as voting) were protesting to express their concerns about a warming planet. As a result, significant media coverage of the protests increased the issue salience of climate policy in the public sphere.…”
Section: The School Strike For Climate Movementmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is important to reflect upon the concept of radical habitus, which arises when agents deal with new experiences that break with their previous expectations or norms, causing them to alter their worldview, thus creating new types of arts of existence and resistance. Alexander et al (2022) state that many young activists began their activism by worrying about environmental causes; however, after seeing the different impacts of their activism, they went on to engage in other activisms related to racial and economic inequalities. This idea can be applied to our cases in the sense that music and music production have given rise to an involvement, from an activist point of view, with other causes, such as feminism, precariousness and Indigenous people.…”
Section: From Working Utopias To a Radical Habitus In Creating Arts O...mentioning
confidence: 99%